Solution- and solid-state NMR studies of GPCRs and their ligands - Tapaneeyakorn, S; Goddard, A; Oates, J; Willis, C; Watts, A (2011)
G protein-coupled receptors (GPCRs) represent one of the major targets of new drugs on the market given their roles as key membrane receptors in many cellular signalling pathways. Structure-based drug design has potential to be the most reliable method for novel drug discovery. Unfortunately, GPCR-ligand crystallisation for X-ray diffraction studies is very difficult to achieve. However, solution- and solid-state NMR approaches have been developed and have provided new insights, particularly focussing on the study of protein-ligand interactions which are vital for drug discovery. This review provides an introduction for new investigators of GPCRs/ligand interactions using NMR spectroscopy. The guidelines for choosing a system for efficient isotope labelling of GPCRs and their ligands for NMR studies will be presented, along with an overview of the different sample environments suitable for generation of high resolution structural information from NMR spectra. © 2010 Elsevier B.V. All rights reserved.